Kebijakan Negara Indonesia terhadap Etnik Tionghoa: Dari Asimilasi ke Multikulturalisme? - Leo Suryadinata (Antropologi Indonesia, 2003)
In many multi-ethnic and multi-religious societies, nation building has often become the urgent task of the government. Under the authoritarian rule of Soeharto, the state introduced an assimilationist policy towards the ethnic Chinese. As the model of the Indonesian nation was based on indigeneity, the ethnic Chinese, considered to be foreign, were expected to be absorbed into the 'native population'. However, after the fall of Soeharto and the rise of a more democratic regime, this policy has been gradually abandoned and multiculturalism has been adopted. This paper aims at examining the evolving concept of the Indonesian nation, the state changing policies towards the ethnic Chinese and the responses of this minority, especially after the fall of the New Order regime. The revival of Chinese ethnicity and the relationship with nation building in the land of the Garuda will also be discussed.